2016
DOI: 10.1080/0886022x.2016.1194164
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin in a triphasic rat model of adenine-induced kidney injury

Abstract: The aim of this study is to investigate whether NGAL, given its advantages over traditional biomarkers, can be used to describe the dynamic characteristics of the renal tubulointerstitial insult caused by adenine. Subsequently, it will be possible to assess NGAL as a biomarker of any acute kidney injury, on top of chronic interstitial disease, if NGAL levels are stable through the chronic phase of our adenine model. Study group rats were fed an adenine diet, and control group rats were fed a regular diet only.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Gil et al, have recently verified the use of NGAL as a reliable renal index in adenine – induced CKD. Other novel markers include KIM-1, cystatin C and VNN1 [45]. The reliability, efficacy, sensitivity and specificity of these renal markers have been shown in recent literature [28].…”
Section: Discussionmentioning
confidence: 99%
“…Gil et al, have recently verified the use of NGAL as a reliable renal index in adenine – induced CKD. Other novel markers include KIM-1, cystatin C and VNN1 [45]. The reliability, efficacy, sensitivity and specificity of these renal markers have been shown in recent literature [28].…”
Section: Discussionmentioning
confidence: 99%
“…Models that have evaluated a single phase of CKD induced by adenine demonstrated an increase in serum NGAL levels relative to controls (Al Za’abi et al, 2018; Ali et al, 2018, 2017). Another study that evaluated a three-phase model of CKD induced by adenine reported a significant increase in serum and urinary NGAL only in the presence of the damage inducer (Gil et al, 2016). In the present study, it was also observed that the serum levels of NGAL increased significantly in the presence of FA; however, as the degree of damage advanced, the NGAL levels decreased even in the presence of the damage inducer.…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins including kidney injury molecule-1 (KIM-1), neutrophil gelatinase associated with lipocalin (NGAL) and cystatin C (Cys-C) also have a major impact on the development of kidney disease. KIM-1, NGAL and Cys-C were originally proposed as markers of AKI, but recently have been used to describe the evolution of CKD (Gil et al, 2016; Lobato et al, 2017). In addition, the omics sciences allow us to evaluate globally the different molecules of a family, rather than a single protein or metabolite, in such a way that the physiological state of an organism can be described by the presence or absence of these molecules (Amaro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Models that have evaluated a single phase of CKD induced by adenine demonstrated an increase in serum NGAL levels relative to controls (Al Za'abi et al 2018;Ali et al 2018;. Another study that evaluated a three-phase model of CKD induced by adenine reported a significant increase in serum and urinary NGAL only in the presence of the damage inducer (Gil et al 2016). In the present study, it was also observed that the serum levels of NGAL increased significantly in the presence of FA; however, as the degree of damage advanced, the NGAL levels decreased even in the presence of the damage inducer.…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins including kidney injury molecule-1 (KIM-1), neutrophil gelatinase associated with lipocalin (NGAL) and cystatin C (Cys-C) also have a major impact on the development of kidney disease. KIM-1, NGAL and Cys-C were originally proposed as markers of AKI, but recently have been used to describe the evolution of CKD (Gil et al 2016;Lobato et al 2017). In addition, the omics sciences allow us to evaluate globally the different molecules of a family, rather than a single protein or metabolite, in such a way that the physiological state of an organism can be described by the presence or absence of these molecules (Amaro et al 2016).…”
Section: Introductionmentioning
confidence: 99%